Fe0.79Si0.07B0.14 metallic glass gaskets for high‐pressure research beyond 1 Mbar. (19th August 2022) - Dong, Weiwei; Glazyrin, Konstantin; Khandarkhaeva, Saiana; Fedotenko, Timofey; Bednarčík, Jozef; Greenberg, Eran; Dubrovinsky, Leonid; Dubrovinskaia, Natalia; Liermann, Hanns-Peter
Abstract : The performance of Fe0.79 Si0.07 B0.14 metallic glass as gasket material is investigated in a number of high‐pressure X‐ray diffraction experiments beyond 1 Mbar using conventional diamond anvil cells (DACs) or toroidal DACs. The combination of high mechanical stability and the smooth scattering background of the amorphous metal enable challenging high‐pressure experiments, and result in a better signal‐to‐noise ratio in challenging powder and single‐crystal X‐ray diffraction studies. Abstract : A gasket is an important constituent of a diamond anvil cell (DAC) assembly, responsible for the sample chamber stability at extreme conditions for X‐ray diffraction studies. In this work, we studied the performance of gaskets made of metallic glass Fe0.79 Si0.07 B0.14 in a number of high‐pressure X‐ray diffraction (XRD) experiments in DACs equipped with conventional and toroidal‐shape diamond anvils. The experiments were conducted in either axial or radial geometry with X‐ray beams of micrometre to sub‐micrometre size. We report that Fe0.79 Si0.07 B0.14 metallic glass gaskets offer a stable sample environment under compression exceeding 1 Mbar in all XRD experiments described here, even in those involving small‐molecule gases ( e.g. Ne, H2 ) used as pressure‐transmitting media or in those with laser heating in a DAC. Our results emphasize the material's importance for a great number of delicate experiments conducted under extreme conditions. They indicate that the application of Fe0.79 Si0.07 B0.14 metallic glass gaskets in XRD experiments for both axial and radial geometries substantially improves various aspects of megabar experiments and, in particular, the signal‐to‐noise ratio in comparison to that with conventional gaskets made of Re, W, steel or other crystalline metals.